Perforator mapping for head and neck reconstructive surgery: a novel personalized approach using magnetic resonance angiography based 3D models and 3D-printing - de Geer, A.F.; Mulder, I.; ter Beek, L.C.; te Boekhorst, A.S.; Plakké, B.I.; Karssemakers, L.H.E.; Dirven, R.; Lohuis, P.J.F.M.; Ruers, T.J.M; Siepel, F.J.; de Koekkoek-Doll, P.K.; van Alphen, M.J.A.; et al. (Frontiers in Oncology, 2025)
BackgroundReconstruction of large head and neck defects in oncologic patients often requires free vascularized tissue flaps. Successful flap design and elevation depend on accurate preoperative identification of perforator vessels. Preoperative Magnetic Resonance Angiography (MRA) could offer detailed insights into perforator course, caliber, origin, and main pedicle length, and thus is expected to surpass conventional handheld Doppler. This study introduces a novel approach for perforator mapping in reconstructive head and neck surgery that integrates MRA with 3D modelling and 3D-printing.MethodsThe proposed workflow comprises four steps: 1) acquisition of contrast-enhanced MRA, 2) construction of a 3D anatomical model, 3) design and 3D-printing of a patient-specific perforator guide, and 4) transfer of perforator locations from the model to the patient’s skin using the guide. To illustrate the clinical feasibility and potential utility of this approach, an initial cohort of patients undergoing perforator flap surgery for oncologic head and neck reconstruction was included. Flap types included fibula free flap (FFF), anterolateral thigh flap (ALT), and medial sural artery perforator flap (MSAP). Intraoperative findings were compared with the 3D models, and surgeons evaluated the models’ usability for virtual planning of flap design and elevation using a five-point Likert scale questionnaire.ResultsTen patients were included for analysis: three FFF, two ALT, and five MSAP cases. In FFF and ALT patients, all perforators intraoperatively used for flap elevation were successfully visualized on MRA and represented in the 3D models. In MSAP patients, small-caliber perforators were not consistently visible. The mean absolute difference between pedicle lengths measured in the 3D models and intraoperatively was 1.0 cm (SD 0.9 cm). The usability questionnaire yielded an average score of 4.2 out of 5, suggesting the potential of MRA-based 3D models for virtual surgical flap planning.ConclusionsThis is the first study to combine preoperative MRA with 3D modelling and 3D-printing for perforator mapping in head and neck reconstruction. The workflow offers a radiation-free, patient-specific planning tool that may enhance surgical precision and support personalized flap design in complex oncological cases.